Multimodality, learning and communication : a social semiotic frame - Bezemer, Josephus Johannes, 1976-; Kress, Gunther R. (London : Routledge, 2016)
'In this book, Gunther Kress and Jeff Bezemer present a new social semiotic theory which brings together communication, learning and identity through detailed analyses of a range of different multimodal environments, including classrooms, textbooks and hospital operating theatres. The world has changed and is changing, economically and technologically, and there is now a mismatch between academic disciplines and the tasks which need to be undertaken. In the light of this, the authors question what is learning, what is communication and what is the place of design in our contemporary world. The approach they develop shows the intrinsic connectedness of different fields of learning; these fields can now be shown as an integrated domain within one theoretical frame. With a focus on a range of socially shaped cultural resources,'modes'; and how people use these'to make (their) meanings material', they describe how different modes and combinations of modes are used, whether in communication or in the achievement of specific tasks. They hypothesize on the effects of the semiotic work that is being done and has been done, and reflect on the constant remaking of the semiotic resources in shaping identity. This book provides students and researchers with a framework which can be used to look at any multimodal environment, whether a dining room, an operating theatre or a classroom. With extensive illustrations and a comprehensive glossary of terms, this book is essential reading for all those working in multimodality, semiotics and related areas'--
Keywords: Modality (Linguistics); Semiotics -- Social aspects; Communication -- Methodology; Social interaction; Oral communication; Language and languages -- Study and teaching